Poéticas virais: questões multimidiáticas na contemporaneidade - Mendonça, Bruno (2012)
The purpose of this research is to study and analyze the viral poetic of interdisciplinary groups which have produced some multimedia and social media actions. To understand this research one has to keep in mind that the viral poetic projects and actions are the ones which investigate and explore the ability to reach out while communicating on the social media by considering the importance of some elements such as the emergency and the autopoiesis . This research presents the timeline and the mapping of these groups artistic manifestations along with an explanation on the project development and on the creative process. The groups which were selected for this research are the ones that use the tools, aids and methodology of mass communication to produce their work while presenting a strong political positioning that spreads out to a macro environment and to the social media as well. The theoretical justification of this research is based on previous studies published by Jussi Parikka, Malcolm Miles and Vilém Flusser and the most recent studies of Cesar Baio and Fabio Oliveira Nunes. We aimed at analyzing their artistic projects, their political, social, economical and cultural extension and the impact produced when they reached out the public. The complexity and the hybridism of these contemporary practices push for an investigation on these artistic movements which have been recently found in the mass communication environment